Applications of nanotechnology in virus detection, tracking, and infection mechanisms. (28th January 2021) - Kang, Jun; Tahir, Ayesha; Wang, Hanjie; Chang, Jin
Abstract: Viruses are among the most infectious pathogens, responsible for the highest death toll around the world. Lack of effective clinical drug for most of the viruses emphasizes the rapid and accurate diagnosis at early stages of infection to prevent rapid spread of the pathogens. Nanotechnology is an emerging field with applications in various domains, where nano‐biomedical science has many significant contributions such as effective delivery of drugs/therapeutic molecules to specific organs, imaging, sensitive detection of virus, and their accurate tracking in host cells. The nanomaterials reported for virus detection and tracking mainly include magnetic and gold NPs, ZnO/Pt‐Pd, graphene, and quantum dots (QDs). In addition, the single virus tracking technology (SVT) allowed to track the life cycle stages of an individual virus for better understanding of their dynamics within the living cells. Inorganic as well as non‐metallic fluorescent materials share the advantages of high photochemical stability, a wide range of light absorption curves and polychromatic emission. Hence, are considered as potential fluorescent nano‐probes for SVT. However, there are still some challenges: (i) clinical false positive rate of some detection methods is still high; (ii) in the virus tracking process, less adaptability of QDs owing to larger size, flicker, and possible interference with virus function; and (iii) in vivo tracking of a single virus, in real time needs further refinement. In the future, smaller, non‐toxic, and chemically stable nanomaterials are needed to improve the efficiency and accuracy of detection, and monitoring of virus infections to curb the mortalities. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Infectious Disease Biology‐Inspired Nanomaterials > Protein and Virus‐Based Structures Abstract : Nano‐particles and their applications in virus detection and tracking to comprehend infection mechanisms.